Perceived motivators and barriers to urban edible gardening among interested non-garderners in Metro Manila - Esmile, Trisha Mariae C. (College of Home Economics, University of the Philippines Diliman, 2023)
Urban agriculture has the potential to address various challenges and offer numerous benefits, including improved food security, dietary diversification, mental health, employment, social bonds, and agricultural literacy. This study focused on exploring the perceived barriers and motivators among interested non-gardeners in Metro Manila while considering the influence of different demographic and contextual factors on perception. Data were collected through an online survey using multiple-choice and Likert scale items. Two hundred respondents completed the survey; more than half of which (n=108, 54%) had prior urban edible gardening experience. Overall, it was found that non-gardeners in Metro Manila have strong motivations for urban edible gardening, with economic motivators taking precedence over other motivators mainly due to the inflation rate in the country and the possibility of saving money on food expenses. Environmental motivators were also one of the top-rated motivators, which indicates a strong desire to be in touch with nature and contribute to helping the environment among the respondents. Health benefits that result from urban edible gardening were also highly considered as a motivator, specifically the respondents perceive the practice to be capable of helping to improve their diet. Meanwhile, the most hindering barrier was found to be concerns about time, with simply having no time and the harvest time taking too long both receiving high ratings. Another highly rated barrier category is that of resources, with respondents mostly expressing that they had no space or enough financial capability to take up the practice. Finally, knowledge barriers were also identified as one of the most hindering barriers, with respondents expressing that they had no guidance since they have no one to ask about edible gardening. Differences found among those who belong to different demographic and contextual groups also indicate that policies should be crafted with the target demographic in mind as a uniform approach may not be effective. This exploratory study offers preliminary insights into the motivators and barriers experienced by urban residents in the Philippines when it comes to edible gardening. The findings serve as a foundation for further research and confirmatory studies in this field. Moreover, the results can be valuable for government agencies and implementing bodies as they would be able to utilize this information to prioritize strategies in order to promote urban edible gardening. Considering the motivators and barriers identified in this study, policymakers can develop targeted initiatives that address the specific needs and concerns of urban residents, thereby fostering greater participation in and support for urban agriculture initiatives.